Implementation of Covid-19 Vaccination Policy At Bhayangkara Hospital Banjarmasin, As An Effort To Maximize The Role of Police In The Community - Hasnilawati Kulle; Ahmad Alim Bachri; Andi Tenri Sompa; Jamaluddin Jamaluddin; Taufik Arbain (International Journal of Politic, Public Policy and Environmental Issues, 2021)
The critical role of the police in a pandemic situation, of course, makes the vaccine implementation program at Bhayangkara Hospital very crucial. The National Police is one of the spearheads in dealing with COVID-19. The protection of the apparatus is an important thing that needs to be considered, including implementing the vaccination policy at Bhayangkara Hospital Banjarmasin. The purpose of this study was to determine the implementation of the COVID-19 vaccination policy. The research focuses on the effectiveness and obstacles faced in implementing vaccinations to handle the COVID-19 Pandemic in South Kalimantan. This research uses a qualitative approach, with the basis of case study research, namely research that is carried out intensively, in detail, and in-depth on a problem that is the object of research. This research is a case study of the COVID-19 vaccination policy, including policy formulation and vaccination implementation. The qualitative approach was carried out using the desk study method, active observation participation, semi-structured interviews, and documentation. This study uses Weimer and Vining's theory because this theory can briefly summarize the various factors that influence policy implementation. These factors include the characteristics of the policy itself, its resources, and the policy environment. The theory can provide an overview for the government in formulating policies so that the established policies can be implemented because the implementation (implementation) of policies is an activity to generate results (output), impact (outcome), benefits (benefits), and impact (impact) that can be enjoyed. By the target group. Implementation of policies vaccines in RS Bhayangkara Banjarmasin already performing well. Even so, keep in mind that vaccines do not automatically mean that COVID-19 will disappear quickly. It takes time to vaccinate the entire population, and The realization of vaccine distribution will have its challenges with the geographical conditions of South Kalimantan, which have various typographical areas. The availability of the vaccine itself is also one of the keys related to its production capacity, affecting the timing of vaccine production for several residents in South Kalimantan